Women, Ethics, and Inequality in U.S. Healthcare “To Count Among the Living” - Vigen, Aana Marie; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2006)
Please note this is a 'Palgrave to Order' title (PTO). Stock of this book requires shipment from an overseas supplier. It will be delivered to you within 12 weeks. When seriously ill, what contributes to a sense of being truly cared for and respected? This compelling book explores healthcare inequalities by listening closely to Black and Latina women with breast cancer. It puts their stories into conversation with current healthcare statistics, sharp theological imagination, healthcare providers, and social ethics. Vigen contends that ethicists, healthcare providers, and scholars arrive at an adequate understanding of human dignity and personhood only when they take seriously the experiences and needs of those most vulnerable due to systemic inequalities.
Keywords: Social policy; Feminist theory; Religion and sociology; Sociology; Gender identity-Religious aspect; Social Policy; Feminism; Sociology of Religion; Gender Studies; Religion and Gender; Social Structure, Social Inequality